Media Sosial Dan Kebijakan Kapolri Mengenai ”Hate Speech” (Ujaran Kebencian) - Satria Kusuma; Djuara P. Lubis (Jurnal Komunikasi Pembangunan, 2016)
The developments of information technologies affect the life of democracy in Indonesia. Information technology such as social media has caused social change. Social media should be a public space to establish relations and public information centers. The user submits a message to create a closer ties with the community and convey information about social problems. The public get information faster from social media rather than print media, radio and television. But there are some people who spread false news (hoaxes) or even attack the other party through hate speech. Such actions lead to defamation toward certain people then lead public opinion to worsen the socio-political situation, causing a split. The insult to the President by a citizen through a message on social media which continues to the proceedings reminds us to be more concerned about the ethical consideration of communication in public spaces. This issue should be a shared responsibility between the organizers and users of social media in order to maintain a cultured communication behavior and ethical understanding. The policy from the head of Indonesian Police regarding hate speech in social media is the firm stance of the government against violators who deliberately spread messages of hate, violate the values, norms, manners and ethics. The act of spreading the message of hate speech is against the law. Hate speech message ruins the conduciveness of social and political situation. This kind of violation could threaten the mentality of younger generations as users of social media in creating a civilized communication in Indonesia.Keywords: hate speech policy, messages of hate, and social media.